2000
DOI: 10.1096/fj.14.10.1279
|View full text |Cite
|
Sign up to set email alerts
|

Rapid production of the major birch pollen allergen Bet v 1 in Nicotiana benthamiana plants and its immunological in vitro and in vivo characterization

Abstract: Type I allergies are immunological disorders that afflict a quarter of the world's population. Improved diagnosis of allergic diseases and the formulation of new therapeutic approaches are based on the use of recombinant allergens. We describe here for the first time the application of a rapid plant-based expression system for a plant-derived allergen and its immunological characterization. We expressed our model allergen Bet v 1, the major birch pollen allergen, in the tobacco-related species Nicotiana bentha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…This prokaryotic expression system is still applied for the production of many different recombinant allergens [103, 104, 105, 106, 107, 108]. In more recent years, several allergens were produced in eukaryotic expression systems like the yeast Pichia pastoris [109, 110, 111, 112, 113, 114, 115, 116, 117, 118, 119, 120, 121, 122, 123, 124, 125, 126, 127], insect cells [128, 129, 130, 131, 132, 133, 134, 135, 136], and tobacco plants [137, 138]. These systems facilitate post-translational modifications that do not (easily) occur in E. coli , like disulfide-bridge formation, hydroxylation of prolines, glycosylation.…”
Section: Recombinant Allergens For Application In Diagnostics and Immmentioning
confidence: 99%
“…This prokaryotic expression system is still applied for the production of many different recombinant allergens [103, 104, 105, 106, 107, 108]. In more recent years, several allergens were produced in eukaryotic expression systems like the yeast Pichia pastoris [109, 110, 111, 112, 113, 114, 115, 116, 117, 118, 119, 120, 121, 122, 123, 124, 125, 126, 127], insect cells [128, 129, 130, 131, 132, 133, 134, 135, 136], and tobacco plants [137, 138]. These systems facilitate post-translational modifications that do not (easily) occur in E. coli , like disulfide-bridge formation, hydroxylation of prolines, glycosylation.…”
Section: Recombinant Allergens For Application In Diagnostics and Immmentioning
confidence: 99%
“…This is the first report of apo-plastic extraction of a recombinant allergen. Previously expressed recombinant allergens (Krebitz et al 2000(Krebitz et al , 2003 have been extracted by grinding leaves in an extraction buffer. Upon using this extraction method for rJun a 3, several contaminating proteins were extracted as well, making vacuum infiltration a much more valuable tool for extraction from plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several recombinant allergens have also been produced in ground leaves of N. benthamiana plants via a tobacco mosaic virus (TMV) vector (Krebitz et al 2000(Krebitz et al , 2003. However, extraction from ground leaves can make purification difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Modern diagnostics of allergic diseases and new therapeutic approaches are based on the use of recombinant allergens [5]. It was shown that Escherichia coli and Nicotiana benthamiana expression systems could be used to produce recombinant allergens with the assigned properties [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Modern diagnostics of allergic diseases and new therapeutic approaches are based on the use of recombinant allergens [5]. It was shown that Escherichia coli and Nicotiana benthamiana expression systems could be used to produce recombinant allergens with the assigned properties [5, 6]. Furthermore, analysis of the 3-dimensional structure identified potential B cell epitopes on the molecular surface of the Bet v 1 protein and thus provided a structural basis for the reactivity of the molecule with IgE antibodies [7].…”
Section: Introductionmentioning
confidence: 99%